Exploring English Education Students’ Challenges in Writing an Introduction for a Journal Article - Mar'atassolihah, Aftina; Widhiyanto, Widhiyanto (Journal of English Language and Education, 2026)
Developing academic writing competence is essential for English education students. This competence is crucial particularly for producing research articles for publication. The introduction section is often perceived as the most challenging part to write. It requires student-writers to establish a research context, engage with previous studies, and clearly state research purposes. In the EFL contexts, these demands are further complicated by some factors as linguistics, rhetorical development, and affective factors. This study examines the challenges encountered by undergraduate English education students in Indonesia when writing research article introductions, focusing on rhetorical organization based on Swales’ (1990) CARS Model. A qualitative research design was employed, involving semi-structured interviews with five seventh-semester students at Universitas Negeri Semarang. The findings reveal varied difficulties across the three rhetorical moves, including limited confidence in establishing research territory, problems synthesizing prior studies and identifying research gaps, and reliance on restricted strategies when presenting research purposes. These findings emphasize the importance of pedagogical support through explicit instruction, scaffolding, and peer feedback to improve students’ academic writing development.